2022
DOI: 10.1371/journal.ppat.1010475
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis requires SufT for Fe-S cluster maturation, metabolism, and survival in vivo

Abstract: Iron-sulfur (Fe-S) cluster proteins carry out essential cellular functions in diverse organisms, including the human pathogen Mycobacterium tuberculosis (Mtb). The mechanisms underlying Fe-S cluster biogenesis are poorly defined in Mtb. Here, we show that Mtb SufT (Rv1466), a DUF59 domain-containing essential protein, is required for the Fe-S cluster maturation. Mtb SufT homodimerizes and interacts with Fe-S cluster biogenesis proteins; SufS and SufU. SufT also interacts with the 4Fe-4S cluster containing prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 72 publications
1
19
1
Order By: Relevance
“…By contrast, in our study, sublethal ampicillin did not have a considerable effect on the OCR and ECFR of S. Typhimurium or the phenotype of yqiC. A study that used the Seahorse Analyzer revealed that the iron-sulfur cluster biosynthesis protein SufT is required for glycolysis, oxidative phosphorylation, and survival in Mycobacterium tuberculosis after exposure to oxidative stress and nitric oxide [61]; this finding echoes our findings regarding the association of yqiC with electron transfer activity, iron-sulfur cluster assembly, and glycolysis in S. Typhimurium. Our RNA-seq analysis revealed the involvement of yqiC in energy and carbohydrate metabolism, and a series of experiments in the Seahorse XFp Analyzer further clarified how yqiC influences cellular respiration and glycolysis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…By contrast, in our study, sublethal ampicillin did not have a considerable effect on the OCR and ECFR of S. Typhimurium or the phenotype of yqiC. A study that used the Seahorse Analyzer revealed that the iron-sulfur cluster biosynthesis protein SufT is required for glycolysis, oxidative phosphorylation, and survival in Mycobacterium tuberculosis after exposure to oxidative stress and nitric oxide [61]; this finding echoes our findings regarding the association of yqiC with electron transfer activity, iron-sulfur cluster assembly, and glycolysis in S. Typhimurium. Our RNA-seq analysis revealed the involvement of yqiC in energy and carbohydrate metabolism, and a series of experiments in the Seahorse XFp Analyzer further clarified how yqiC influences cellular respiration and glycolysis.…”
Section: Discussioncontrasting
confidence: 99%
“…Typhimurium or the phenotype of yqiC . A study that used the Seahorse Analyzer revealed that the iron–sulfur cluster biosynthesis protein SufT is required for glycolysis, oxidative phosphorylation, and survival in Mycobacterium tuberculosis after exposure to oxidative stress and nitric oxide [ 61 ]; this finding echoes our findings regarding the association of yqiC with electron transfer activity, iron–sulfur cluster assembly, and glycolysis in S . Typhimurium.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The E. coli Isc system is generally poisoned with as low as 1 μM H 2 O 2 , whereas the Suf system remains resistant to oxidative stress (6). Similar differences in sensitivity to oxidants are expected for Mtb IscS and Suf systems (10,11,17). However, the artificial overproduction of IscS suppresses the growth defect of MtbΔiscS and renders the mutant more resistant to H 2 O 2 than WT Mtb (17).…”
Section: Discussionmentioning
confidence: 77%
“…SufT is proposed to act as an accessory factor in Fe-S biogenesis in Mtb, since it is dispensable for growth of Mtb under standard culture conditions, required under conditions of iron limitation [170], and SufT loss does not increase susceptibility to oxidative stress [170]. Very recently, Mtb SufT protein was shown to interact with SufS and SufU and to maintain the activity of Fe-S cluster proteins during normal growth conditions, and under environmental settings that enforce a high demand of Fe-S clusters [171]. Characterizations of Mtb SufS and SufU will certainly provide additional information and interesting insights into the sulfur production.…”
Section: Activation Of Mtb Fe-s Biogenesis and Metabolism Upon Ros No...mentioning
confidence: 99%